DETERMINATION AND ASSESSMENTS OF PHYSICO-CHEMICAL PARAMETERS OF THE WATER FROM ANTHROPO-SALINE LAKES LOCATED IN THE PROTECTED AREA “SALINA TURDA”, ROMANIA - RUS, Liliana; AVRAM, Simona-Elena; MICLE, Valer (Studia Universitatis Babeș-Bolyai Chemia, 2020)
It was carried out the monitoring of the qualitative parameters for the Ocnei and Rotund lakes located in the protected area Salina Turda, Romania, and as well it was made a comparative analysis of the results with previous determinations. It was determined the evolution of the physico-chemical parameters on 5 segments of depth. The monitoring was carried out within 2 measurement campaigns. It has been determined that the lakes tend to lose basicity and it was found that the heliotherm phenomenon represents a stable index in comparison with previous determinations.